2013
DOI: 10.1021/la400910g
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Is Important for the Helicity of the Self-Assemblies of Dipeptides Derived from Alanine

Abstract: The organization of peptides and proteins attracts much attention, due to the biofunctionalities of the self-assemblies. Herein, four dipeptides derived from alanine were synthesized. It was found that the handedness of their self-assemblies was controlled by the chirality of the alanines at the terminals. The organic self-assemblies were studied using circular dichroism, (1)H NMR, Fourier transform infrared, field-emission electron microscopy, transmission electron microscopy, and X-ray diffraction. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 30 publications
7
110
0
1
Order By: Relevance
“…Remarkably, homochiral LL and DD peptide-modified NDIs self-assembled into 1D hierarchical supramolecular polymers with opposite helicity, while the heterochiral peptide conjugates LD and DL formed microspheres. 141 Yang et al 142 reported an interesting control of handedness of the alanine dipeptide self-assemblies by the chirality of the were right-handed. The morphologies of the assemblies were consistent with the CD spectral data, which also indicated that the handedness of these organic selfassemblies was controlled by the chirality of the alanines at the terminals.…”
Section: Gemini Amphiphiles and Bolaamphiphilesmentioning
confidence: 99%
“…Remarkably, homochiral LL and DD peptide-modified NDIs self-assembled into 1D hierarchical supramolecular polymers with opposite helicity, while the heterochiral peptide conjugates LD and DL formed microspheres. 141 Yang et al 142 reported an interesting control of handedness of the alanine dipeptide self-assemblies by the chirality of the were right-handed. The morphologies of the assemblies were consistent with the CD spectral data, which also indicated that the handedness of these organic selfassemblies was controlled by the chirality of the alanines at the terminals.…”
Section: Gemini Amphiphiles and Bolaamphiphilesmentioning
confidence: 99%
“…3 ). This work showed that the chirality of the C -terminal amino acid dictates the chiral orientation of the supramolecular helical nanoribbons, with on one hand the L Ala- D Ala derivative having the same handedness as the D Ala- D Ala counterpart, and on the other hand the D Ala- L Ala derivative having the same handedness as the L Ala- L Ala analogue [38]. …”
Section: Effects On Self-assembly and Gelationmentioning
confidence: 99%
“…They were longer than 2 ”m and entangled with each other to form 3D networks for hydrogel formation. The examples of helical nanofibers in hydrogels were rare [51]–[55], and the helical nanofibers in this hydrogel might be useful as templates for the preparation of helical organic and in-organic nano-materials.…”
Section: Resultsmentioning
confidence: 99%